sec^2xcotx-cotx=tanx

(1/cos)^2 times (1/tan)-(1/tan)=tan

(1/cos^2) times (-2/tan)=tan

(-2/cos^2tan)times tan=tan(tan)

sq. root of (-2/cos^2)= sq. root of (tan^2)

sq. root of (2i)/cos=tan

I'm not sure if I did this right. If I didn't, can you show me the correct steps?

Thanks, I appreciate it.

2 answers

sec^2(x)cot(x) - cot(x) = tan(x)

Convert everything to sine and cosine using the identity tan(x) = sin(x)/cos(x).

cos^-2(x)(cos(x)/sin(x)) - cos(x)/sin(x) = sin(x)/cos(x)

1/( cos(x)sin(x) ) - cos(x)/sin(x) = sin(x)/cos(x)

Note: it is important to write sin(x) as opposed to sin, because you may find equations that include different parameters -- sin(x) and sin(2x), for example.
tan7.50
Similar Questions
  1. Operations with Radical Expressions1. Simplify the expression: 4 times Start Root 18 End Root plus 5 times Start Root 32 End
    1. answers icon 1 answer
  2. Simplify the radical expression.Square root 56 times x squared (1 point) Responses 28x 28 x 2 times x times square root 14.
    1. answers icon 1 answer
    1. answers icon 1 answer
  3. S equals square root of 30 times D times f times n end rootWhere: S = speed in miles per hour 30 = a constant value used in the
    1. answers icon 1 answer
more similar questions